Effect of road safety information availability and utilisation on commercial motorcycle accidents in Nigeria (2013)
The availability of information on road safety on Nigerian roads especially by commercial motorcycle riders has been the subject of discussion by road transport administrators, medical practitioners and the media as a result of unsatisfactory performance. There is a general expression of dissatisfaction by users of services rendered by the commercial motorcyclists on our roads. As a result, the pedestrians have complained of the riding pattern of the motorcyclists, alcoholic drinking pattern, overconfidence, over speeding, effects of bad roads, and lack of understanding of road signs as factors influencing road accidents by commercial motorcyclists. However, there is paucity of research on road safety among commercial motorcyclists in Nigeria. It is against this background that this research examines the effect of road safety information availability on commercial motorcycle accidents in Nigeria. Simple Random Technique was used to cover a study population of four hundred and fifty (450) commercial motorcycle riders in Oyo State, Nigeria. Demographic data and road safety information availability were looked into. Data collected were analyzed using percentages, mean and standard deviation. The result revealed that road safety information is available to the population studied. However, its effect could not be traced. 337 respondents claimed to have had accident at one time or the other. 81.8% respondents do not possess a copy of the Nigeria Highway Codes which ought to serve as guides in the prevention of accident among the commercial motorcyclists. Few recommendations are given.